Development of an Institutional Periprocedural Management Guideline for Oral Anticoagulants. Issue 4 (December 2020) - Lewin, Andrea R.; Collins, Peter E.; Sylvester, Katelyn W.; Rimsans, Jessica; Fanikos, John; Goldhaber, Samuel Z.; Connors, Jean M.
Abstract : Patients on oral anticoagulation commonly undergo surgery or other invasive procedures. Periprocedural management of oral anticoagulants involves a careful balance of the thromboembolic risk and bleeding risk. To standardize clinical practice at our institution, we developed a guideline for periprocedural management for patients taking oral anticoagulants that incorporates published data and expert opinion. In this article, we present our clinical practice guideline as a decision support tool to aid clinicians in developing a consistent strategy for managing periprocedural anticoagulation and for safely bridging anticoagulation in patients who require it.